2019
DOI: 10.1042/bsr20190615
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SAMMSON negatively regulates miR-9-3p in hepatocellular carcinoma cells and has prognostic values

Abstract: In the present study, we investigated the role of lncRNA SAMMSON in hepatocellular carcinoma (HCC). We found that SAMMSON was up-regulated in HCC tissues, and patients with high levels of SAMMSON in HCC tissues had significantly lower overall rate within 5 years after admission. miR-9-3p was down-regulated in HCC tissues and inversely correlated with SAMMSON. SAMMSON expression was not significantly affected by HBV and HCV infections in HCC patients. In HCC cells, SAMMSON overexpression resulted in down-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…miR-9-3p has been confirmed as a tumor suppressor in a variety of different types of cancer, such as glioma ( 47 ), nasopharyngeal carcinoma ( 48 ) and bladder cancer ( 49 ). Of interest, in HCC cells, Yang et al ( 50 ) demonstrated that miR-9-3p overexpression reduced the migration and invasion rates of HCC in vitro . Tang et al ( 51 ) demonstrated that miR-9-3p, a functional biomarker, inhibited cell proliferation by suppressing human fibroblast growth factor-5 expression in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…miR-9-3p has been confirmed as a tumor suppressor in a variety of different types of cancer, such as glioma ( 47 ), nasopharyngeal carcinoma ( 48 ) and bladder cancer ( 49 ). Of interest, in HCC cells, Yang et al ( 50 ) demonstrated that miR-9-3p overexpression reduced the migration and invasion rates of HCC in vitro . Tang et al ( 51 ) demonstrated that miR-9-3p, a functional biomarker, inhibited cell proliferation by suppressing human fibroblast growth factor-5 expression in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…evidence has indicated that over-expression of miR-9-5p could enhance cell migration and invasion while miR-9-3p could inhibit cell migration an invasion in HCC cells [20,31]. However, in this study, we revealed that miR-9-5p was a suppressor, we had examined the level of miR-9 and found that it was lower in cancer tissue than that in normal tissue and up-regulation of miR-9 could enhance sensitivity to cisplatin in HCC cells.…”
Section: Accumulatedmentioning
confidence: 99%
“…It has been reported that aberrantly expressed long non-coding RNAs (lncRNAs) were aberrantly expression in the occurrence and development of HCC, which are identi ed as the oncogenes or tumor suppressors. For example, SAMMSON expression level was upregulated in HCC tissues, and patients with high SAMMSON level had signi cantly lower overall rate within ve years after admission (6).…”
Section: Introductionmentioning
confidence: 99%